2018
DOI: 10.21093/ijeltal.v3i1.115
|View full text |Cite
|
Sign up to set email alerts
|

Cognitions and Practices of Iranian ELT Instructors and Content Teachers in Teaching Discipline-Based EAP Courses: A Replication Study

Abstract: Although research studies on methodological issues of English for General Purposes are abundant in the literature, they are still one of the less explored areas of research in English for Academic Purposes, especially with respect to teachers’ cognitions and practices. Also, lack of collaboration between ELT instructors and content teachers in teaching discipline-based EAP courses has resulted in noticeable inconsistencies in the two groups’ instructions. The present study was an extension of Atai and Fatahi-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Further, it investigated the practices and cognitive approaches among six ELT teachers and six academic subject teachers during the delivery of EAP courses and class activities. Consistent with Atai and Fatahi-Majd (2014), Soleimani and Alibabaee (2018) found that there were substantial inconsistencies and considerable discrepancies in teachers' practices. Those results highlight the need to incorporate new ideas and reflection on the consistency of EAP teaching practices and cognitions.…”
Section: Practices Of Elt Instructors and Subject Teachers Within The...mentioning
confidence: 54%
See 1 more Smart Citation
“…Further, it investigated the practices and cognitive approaches among six ELT teachers and six academic subject teachers during the delivery of EAP courses and class activities. Consistent with Atai and Fatahi-Majd (2014), Soleimani and Alibabaee (2018) found that there were substantial inconsistencies and considerable discrepancies in teachers' practices. Those results highlight the need to incorporate new ideas and reflection on the consistency of EAP teaching practices and cognitions.…”
Section: Practices Of Elt Instructors and Subject Teachers Within The...mentioning
confidence: 54%
“…A recent study by Soleimani and Alibabaee (2018) acknowledged the extension of the discussion by Atai and Fatahi-Majd (2014). Further, it investigated the practices and cognitive approaches among six ELT teachers and six academic subject teachers during the delivery of EAP courses and class activities.…”
Section: Discussionmentioning
confidence: 99%